The role of cellular heterogeneity in thyroid cancer: a multi-modal analysis approach with Mendelian randomization - Yichun Qian; Wei Chen; Xinyuan Chen; Shuai Cheng; Fangzhou Liu (Discover Oncology)
Abstract Background Thyroid cancer pathogenesis involves complex interactions between genetic predisposition and alterations in the tumor microenvironment. The causal relationships between inflammatory gene variants and thyroid cancer risk remain poorly understood, as does the cellular heterogeneity within the tumor ecosystem. This study aimed to investigate the causal associations between inflammatory protein genes and thyroid cancer risk, and to characterize the cellular composition and differentiation trajectories within the thyroid cancer microenvironment. Methods We employed a two-pronged approach combining Mendelian randomization (MR) analysis and single-cell RNA sequencing (scRNA-seq). MR analyses were conducted using genetic variants associated with the expression of inflammatory proteins (4EBP1_EIF4EBP1, ADA_ADA, ARTN_ARTN, AXIN1_AXIN1, and Beta-NGF_NGF) as instrumental variables to assess their causal effects on thyroid cancer risk. Multiple MR methods (MR Egger, weighted median, inverse variance weighted, simple mode, and weighted mode) were used to enhance robustness. For the cellular characterization, scRNA-seq was performed on thyroid cancer samples, followed by dimensionality reduction, clustering analysis, cell type annotation, and pseudotime trajectory inference. Results MR analyses revealed a significant positive causal association between AXIN1_AXIN1 expression and thyroid cancer risk (weighted median: OR = 1.396, p < 0.05; inverse variance weighted: OR = 1.291, p < 0.05), while ADA_ADA showed protective effects (simple mode: OR = 0.731, p < 0.05). The scRNA-seq analysis identified six major cell populations within the thyroid cancer microenvironment: epithelial cells, T cells, natural killer cells, fibroblasts, stromal cells, and macrophages. Pseudotime analysis revealed distinct differentiation trajectories with natural killer cells and macrophages appearing in early pseudotime, while epithelial cells and fibroblasts demonstrated multiple developmental states. Gene expression profiling identified four distinct cellular states with unique molecular signatures, including immune/inflammatory, stromal, and vascular components. Conclusion Our findings suggest that inflammatory protein genes, particularly AXIN1, have causal effects on thyroid cancer risk, providing potential targets for risk prediction and intervention.